1986
DOI: 10.2118/11217-pa
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Relative Permeability and Its Effect on Oil Displacement by Thermal Methods

Abstract: An analytical theory is presented that permits the formulation of a mathematical model to describe the variation of relative permeability with temperature in a water/oil system. The theory develops analytical equations for temperature-dependent relative permeability in terms of water saturation, irreducible water saturation, and differential change in irreducible water saturation with temperature. These equations predict and agree reasonably well with experimental results reported by other researchers.The impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…The absolute permeability was reduced by almost 50% in all cases as shown in Table 5, where the temperature increased to 130°C. This is in agreement with the statement by Nakornthap and Evans [19], that Cassé and Ramey [25], Weinbrandt et al [26], and Gray et al [27] found that absolute permeability decreases with temperature. Sedaee Sola et al [28] reported that limestone showed a more oil-wet (as indicated by a shift of the relative permeability curves) behavior when temperature increased to …”
Section: Mutual Solubility Datasupporting
confidence: 92%
See 3 more Smart Citations
“…The absolute permeability was reduced by almost 50% in all cases as shown in Table 5, where the temperature increased to 130°C. This is in agreement with the statement by Nakornthap and Evans [19], that Cassé and Ramey [25], Weinbrandt et al [26], and Gray et al [27] found that absolute permeability decreases with temperature. Sedaee Sola et al [28] reported that limestone showed a more oil-wet (as indicated by a shift of the relative permeability curves) behavior when temperature increased to …”
Section: Mutual Solubility Datasupporting
confidence: 92%
“…In general from this work and the work done by Nakornthap and Evans [19], it may be concluded that use of room temperature relative permeability underestimates the oil recovery rate and ultimate recovery. It may, also, be concluded that not only the injected fluid temperature that affect the recovery rate and ultimate recovered oil but also temperature difference between the injected fluid and the reservoir temperature.…”
Section: Oil Recovery Sensitivity To Different Temperature Relative Pmentioning
confidence: 52%
See 2 more Smart Citations
“…Early thermal modeling suggested that temperature dependence of relative permeability must be incorporated into the model to reproduce experimental results (Coats et al, 1974). Review of the early literature on the effects of temperature on relative permeability suggests the following (Nakornthap and Evans, 1986): ! Relative permeability can be expressed in terms of water saturation and irreducible water saturation.…”
Section: Modelingmentioning
confidence: 99%